Moderator role of Type D personality traits between depressive symptoms and job satisfaction among teachers - Yetkin Tekin, Ayşegül; Karadağ, Hekim (Frontiers in Public Health, 2024)
Background: Type D personality is characterized by negative affect (NA) and social suppression (SI). It has been indicated Type D personality is associated with depression, anxiety, and burnout. Depressive complaints and social inhibition negatively affect job satisfaction. The aim of this study is to investigate the moderating role of Type D personality structure between the severity of depressive complaints and job satisfaction in teachers. Methods: 939 teachers, who constitute the sample of the study, completed the sociodemographic form, Type D personality scale (DS-14), Beck Depression Inventory (BDI) and Minnesota Satisfaction Scale Short Form with an online survey.Results: While a negative relationship was found between teachers' NA scores and their intrinsic and extrinsic job satisfaction (r=-.28 and r=-.19, respectively), a negative relationship was detected between SI scores and intrinsic and extrinsic job satisfaction (r=-.22 and r=-.21, respectively). NA and SI had partial moderating roles in the relationship between BDI score and intrinsic job satisfaction. SI played a partial moderating role in the relationship between BDI and extrinsic job satisfaction.It can be said Type D personality traits has a moderating role between the severity of teachers' depressive complaints and job satisfaction.